Conflict Resolution Strategies in Kampung Naga Indigenous Community: Preserving Tradition in the Face of Modernity - Budi Yasri; Asep Ridwan Lubis; Vera Firmansyah; Gianto Gianto; Nandang Gunawan Tunggal Waras; Kartika Nurul Aulia (Universitas Pendidikan Ganesha, 2024)
This study examines conflict resolution strategies within the Kampung Naga indigenous community. It focuses on how traditional governance systems—particularly adat law—function alongside state law to mediate conflicts and preserve cultural integrity amidst modernization pressures. Employing a descriptive qualitative method, this research draws on in-depth interviews, participant observations, and document analysis to reveal the community’s dual governance system. Findings indicate that Kampung Naga’s adherence to adat law fosters social cohesion and leads to generational tensions, particularly regarding land use and economic integration. The study demonstrates that while traditional mechanisms remain effective for resolving internal disputes, external conflicts, such as land disputes with government entities, require a hybrid approach incorporating state law. This duality illustrates the resilience of Kampung Naga’s cultural practices and the challenges they face in balancing modern legal frameworks. The practical implications of this research extend to broader discussions on preserving indigenous governance systems in the face of state legal integration and economic pressures. These findings offer critical insights into how traditional societies can maintain cultural autonomy while navigating external influences, contributing to theoretical and practical debates on conflict resolution and indigenous governance.